2014
DOI: 10.1002/bjs.9593
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and meta-regression analysis of biomarkers for abdominal aortic aneurysm

Abstract: A wide variety of biomarkers are dysregulated in patients with AAA, but their clinical value is yet to be established. Future research should focus on the most relevant biomarkers of AAA, and how they could be used clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 127 publications
(525 reference statements)
2
55
2
2
Order By: Relevance
“…These include markers related to thrombus remodeling (eg, D-dimer), the extracellular matrix (eg, aminoterminal propeptide of type III procollagen), proteolytic enzymes (eg, matrix metalloproteinase-9), lipids (eg, high-density lipoprotein), and inflammation (eg, interleukin-6). 53,54 In contrast, there have been fewer studies investigating circulating markers associated with AAA progression. Studies of this type are difficult to design and carry out for many reasons.…”
Section: Current Research To Identify Circulating Markers Of Aaa Progmentioning
confidence: 99%
“…These include markers related to thrombus remodeling (eg, D-dimer), the extracellular matrix (eg, aminoterminal propeptide of type III procollagen), proteolytic enzymes (eg, matrix metalloproteinase-9), lipids (eg, high-density lipoprotein), and inflammation (eg, interleukin-6). 53,54 In contrast, there have been fewer studies investigating circulating markers associated with AAA progression. Studies of this type are difficult to design and carry out for many reasons.…”
Section: Current Research To Identify Circulating Markers Of Aaa Progmentioning
confidence: 99%
“…Most commonly, investigators have measured blood concentrations of analytes to assess its possible role in the pathogenesis or progression of AAA, 8,18,19 and recently Folsom et al. 16 found that multiple positive biomarkers of inflammation identify a subgroup of patients at high risk of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and epidemiological studies consistently link low HDL cholesterol levels to an elevated risk of cardiovascular disease. A recent meta-analysis also revealed a negative association of HDL cholesterol levels with AAA in most studies10. HDLs are additionally a transport platform for constitutive and non-permanently associated plasma proteins.…”
mentioning
confidence: 91%